Natação e treinamento de força: influências sobre a expressão gênica de TNF-alfa e IL-10, área de adipócitos e perfil lipídico em ratos obesos - Speretta, Guilherme Fleury Fina (2011)
The aim of the present study was to investigate the effect of swimming and resistance training exercise on adipose tissue, inflammation and lipid profile in highfat feeding rats. Wistar adult male rats were divided into 6 groups (n = 10 per group): Sed-C, sedentary chow diet; Sed-HL, sedentary high-fat diet; NT-C, swimming chow diet; NT-HL, swimming high-fat diet; TF-C, resistance training chow diet; TF-HL resistance training high-fat diet. An 8-week training period was used. During it period the animals of resistance training groups climbed a 1.1-m vertical ladder with weights attached to their tails. The sessions were performed once every 3 days, with 4 9 climbs and 8 12 dynamic movements per climb. Swimming groups performed 60 min/day, 5 days a week, with a constant overload of 5% body weight during 8 weeks in tanks of 50 cm of height and 30 cm of diameter. High fat-diet increased body weight, relative weight of adipose tissue (epididymal, retroperitoneal, visceral and subcutaneous) and adipose tissue area (epididymal, retroperitoneal and visceral). There was higher TNF-alpha expression and lower (not significant) IL-10 expression in visceral adipose tissue and negative change in lipid profile because of the high-fat diet. Resistance training presented lower values of visceral and retroperitoneal adipocyte area, lower TNF-alpha expression and changed lipid profile. Swimming presented lower epididymal and retroperitoneal adipocyte area, higher IL-10 expression and changed lipid profile. These results indicate the potential benefits of resistance training and swimming as non pharmacological alternatives to control the effects of high-fat diet on adipocyte area, lipid profile and inflammatory process in rats.